2023
DOI: 10.3389/fphar.2023.1218703
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy related hormones increase CYP3A mediated buprenorphine metabolism in human hepatocytes: a comparison to CYP3A substrates nifedipine and midazolam

Abstract: Introduction: Pregnancy increases the clearance of CYP3A4 substrate drugs and pregnancy-related hormones (PRHs) induce hepatic CYP3A4 expression and metabolism. However, it remains unclear to what extent the magnitude of PRH-evoked changes in hepatic CYP3A metabolism varies across multiple substrates. This study quantified the impact of PRHs on CYP3A protein concentrations and buprenorphine metabolism in human hepatocytes, and compared the magnitude of these effects to nifedipine and midazolam metabolism.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Because hepatic NNMT and AOX1 play a critical role in NAM metabolism, 14,15 in vitro experiments in human primary hepatocytes were completed to determine whether pregnancy related hormones (PRHs) alter hepatic NNMT or AOX1 expression. Experimental conditions for hepatocyte culture, PRH treatment, cytosolic protein fractionation, and targeted absolute protein concentration quantification were completed as previously described 35,36 . Briefly, sandwich‐cultured human hepatocytes (SCHHs) from 5 female donors (age 18–49 years) were exposed to vehicle control, or a cocktail of PRHs (estrone, estradiol, estriol, progesterone, cortisol, and placental growth hormone) that target average trimester 2 (T2), average trimester 3 (T3), and upper range of T3 (T3‐90%) maternal plasma concentrations for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Because hepatic NNMT and AOX1 play a critical role in NAM metabolism, 14,15 in vitro experiments in human primary hepatocytes were completed to determine whether pregnancy related hormones (PRHs) alter hepatic NNMT or AOX1 expression. Experimental conditions for hepatocyte culture, PRH treatment, cytosolic protein fractionation, and targeted absolute protein concentration quantification were completed as previously described 35,36 . Briefly, sandwich‐cultured human hepatocytes (SCHHs) from 5 female donors (age 18–49 years) were exposed to vehicle control, or a cocktail of PRHs (estrone, estradiol, estriol, progesterone, cortisol, and placental growth hormone) that target average trimester 2 (T2), average trimester 3 (T3), and upper range of T3 (T3‐90%) maternal plasma concentrations for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the expression and activity of hepatic CYP enzymes is modulated by pregnancy-related hormones (including estrogen, progesterone and cortisol), which increase progressively during pregnancy. Fashe et al demonstrated that the exposure of sandwich-cultured human hepatocytes from adult female donors to pregnancy-related hormones, at concentrations akin to those observed during the third trimester in vivo, resulted in a 2.34 ± 0.48-fold increase in CYP3A4 protein concentrations [ 11 ]. This increase is remarkably consistent with the observed third trimester increase in the oral (unbound) clearance of midazolam [ 12 ].…”
Section: Lessons Learned and Future Perspectivesmentioning
confidence: 99%